Pain and the biochemistry of fibromyalgia: patterns of peripheral cytokines and chemokines contribute to the differentiation between fibromyalgia and controls and are associated with pain, fat infiltration and content - Gerdle, Björn; Dahlqvist Leinhard, Olof; Lund, Eva; Lundberg, Peter; Forsgren, Mikael Fredrik; Ghafouri, Bijar (Frontiers in Pain Research, 2024)
Objectives: This explorative study analyses interrelationships between peripheral compounds in saliva, plasma, and muscles together with body composition (BC) variables in healthy subjects and in fibromyalgia patients (FM). There is a need to better understand the extent cytokines and chemokines are associated with body composition and which cytokines and chemokines differentiate FM from healthy controls.Here, 32 female FM patients and 30 age-matched female healthy controls underwent a clinical examination that included blood sample, saliva samples, and pain threshold tests. The subjects completed a health questionnaire. From these blood and saliva samples, a panel of 68 mainly cytokines and chemokines were determined.Microdialysis of trapezius and erector spinae muscles, phosphorus-31 magnetic resonance spectroscopy of erector spinae muscle, and whole-body magnetic resonance imaging for determination of BC -i.e., muscle volume, fat content and infiltrationwere also performed.After standardizing BC measurements, fat infiltration and content are increased, and fat-free muscle volume is decreased in FM. Mainly saliva proteins differentiated FM from controls. When including all investigated compounds and BC variables, fat infiltration and content variables were most important, followed by muscle compounds and cytokines and chemokines from saliva and plasma. Various plasma proteins correlated positively with pain intensity in FM and negatively with pain thresholds in all subjects taken together. A mix of increased plasma cytokines and chemokines correlated with an index covering fat infiltration and content in different tissues. When muscle compounds were included in the analysis, several of these were identified as the most important regressors, although many plasma and saliva proteins remained significant.Discussion: Peripheral factors were important for group differentiation between FM and controls. In saliva, cytokines and chemokines were significantly associated with group membership as saliva compounds were increased in FM. The importance of peripheral factors for group differentiation increased when muscle compounds and BC variables were included. Plasma proteins were important for pain intensity and sensitivity. Plasma cytokines and chemokines mainly were also significantly and positively associated with a fat infiltration and content index.Our findings of associations between cytokines and chemokines and fat infiltration and content in different tissues confirm that inflammation and immune factors are secreted from adipose tissue.